Pressure dependence of effective dynamic charge in InxAl1-xAs ternary alloys - Park, Ta-Ryeong; Kim, Young Dong; Song, Jin Dong (PERGAMON-ELSEVIER SCIENCE LTD, 2015)
Using Raman scattering data under high pressure, we show that InxAl1-xAs ternary alloys exhibit, depending on In molar fraction x, either decreasing or increasing effective dynamic charge for InAs-like mode with increasing pressure. The variation of the effective dynamic charge in ternary alloy is determined by two factors: (1) the charge transfer between two different vibrating pairs and (2) the tendency to reduce it under lattice contraction in binary case. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: HYDROSTATIC-PRESSURE; INP1-XASX ALLOYS; ALAS; SCATTERING; GAAS; INP